The Effectiveness of the Sizerebotif Multimedia Filter Method in Improving the Quality of Dug Well Water to be Clean Water for Communities in Sinjai Regency - Mulyadi, Mulyadi; Zaenab, Zaenab; Khaer, Ain; Mappau, Zrimurti; Adam, Adriyani (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Based on the results of laboratory examinations, initial samples taken from one of the clean water sources (dug wells) in Biringere Village, North Sinjai District, results showed that the water sample contained high enough metal ions such as Fe, Mn, hardness, and organic substances which did not meet the requirements as clean water because it still contained levels of Manganese (Mn) 1.68 mg/l. Meanwhile, for organic substances (KMnO4), it is 9876 mg/l. AIM: The purpose of the research was to determine the effectiveness of multimedia filters in improving quality of clean water from the parameters of Mn and KMnO4 in clean water sources (dug wells).. METHODS: The type of research conducted is quasi-experimental by made a filtering processing method with a “Up Flow” flow system, using media consisting of silica sand, zeolite, resin (pine resin), and active carbon in PVC tubes. The population in this study were all dug wells in North Sinjai district. The samples were dug wells located on Biringere Village, North Sinjai District. The samples examined in Center for Environmental Health and disease control of Makassar. RESULTS: The results obtained were that there was a significant change in manganese (Mn) levels of 0.49 mg/l (80.37%). Meanwhile, organic substances (MnO4) amounted to 17.38 mg/l (70.02%). CONCLUSION: Decreasing levels of manganese (Mn) in well water after going through the multimedia filter process above show that the manganese content has met the standard requirements of the Minister of Health Regulation No. 32 of 2017.